A Comparative Analysis of Acute Kidney Injury Incidence in Patients Treated with Vancomycin in Combination with Piperacillin-Tazobactam or Meropenem (Medical Forum Monthly, 2023)
Objective: To compare the percentage of postoperative sensitivity between amalgam and composite in patients undergoes dental restorative treatment.Study Design: Randomized Control Trial studyPlace and Duration of Study: This study was conducted at the Department of Operative Dentistry, Bibi Aseefa Dental College @ Shaheed Mohtarma Benazir Bhutto Medical University, Larkana, Sindh, from March 2022 to February 2023.Materials and Methods: Permission was taken from the ethical committee of the hospital. .Fully informed written consent was taken from all the patients. Complete history and physical examination was carried out in all the patients. Patients were divided into two groups, group A was treated with composite material and B was treated with amalgam restorative material. SPSS version 23 was used for data analysis. Tests of significance chi square and t-test were applied. P-value < 0.05 was taken as statistically significant.Results: POS after 24 h was 15.0%, 38.5%, 47.6% for shallow, medium, and deep cavities, respectively with no significant differences (P > 0.05). However, in all studied periods the percentage was 8.8%, 14.6%, 22.6% for shallow, medium, and deep cavities, respectively and revealed significant differences (P < 0.05).Conclusion: It is concluded that POS% (Postoperative Sensitivity) is higher in amalgam restorations particularly in deep cavities and it doesn’t depends on preparation design.